The Compatibility of Al-‘Arabiyyah Baina Yadaik Textbook Volume I with Adolescent Cognitive Psychology - Tsania Sausan Hasna; Muhajir Muhajir (Indonesian Journal of Arabic Studies, 2024)
Purpose: This study seeks to evaluate the compatibility of the Al-‘Arabiyyah Baina Yadaik Volume I textbook with adolescent cognitive psychology. Specifically, it examines the suitability of its material presentation, language use, and exercise questions in relation to the cognitive developmental stages of adolescents. Methods: The research employs a library-based methodology, utilising documentation as the primary data collection technique. Content analysis was conducted on the Al-‘Arabiyyah Baina Yadaik Volume I textbook, which served as the primary data source. Secondary sources include books and other materials relevant to the study. Findings: The analysis of Al-‘Arabiyyah Baina Yadaik Volume I reveals that it is well-suited for use as an Arabic language textbook for seventh-grade junior high school students. The presentation of material, linguistic choices, and exercise formats align with Jean Piaget's theory of adolescent cognitive development, which emphasises logical thinking abilities. Research Implications: This research underscores the significance of tailoring Arabic language learning materials to foster logical reasoning while addressing students' emotional needs to enhance motivation and learning efficacy. However, the study's scope is confined to the textbook's content and structure, without accounting for external factors such as cultural, social, or classroom dynamics. Moreover, its relevance is limited to junior high school students in Indonesia, which may reduce its applicability to broader educational contexts.